2011
DOI: 10.1128/jcm.00372-11
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Genotyping of Enterocytozoon bieneusi in China

Abstract: In this study, the prevalence of Enterocytozoon bieneusi in China was investigated. Twelve genotypes of E. bieneusi were identified, of which 10 were novel genotypes. Further, 41.6% of the genotypes were found in both humans and animals. This is the first report of E. bieneusi in China.Microsporidia are a diverse group of obligate intracellular pathogens consisting of approximately 1,300 formally described species in 160 genera that infect a wide range of invertebrate and vertebrate hosts, including humans (8,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
165
5
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(184 citation statements)
references
References 18 publications
13
165
5
1
Order By: Relevance
“…Two recent studies in central China reported the occurrence of E. bieneusi in 5.7% (39/683) of adult AIDS patients, 4.2% (29/683) of HIV-negative adult participants, 10.8% (8/74) of hospitalized case children with an average age of 20.7 months, and 3.2% (16/499) of control children with an average age of 42.6 months (8, 9). The pathogen was also detected in 22.5% (9/40) of in-hospital children with diarrhea (age unknown) in Changchun (10). The present study ascertained infection with the organism in diarrheic (25%, 1/4) and nondiarrheic (22.2%, 8/36) in-hospital children mostly aged Ͻ12 months and 5.6% (10/178) of healthy primary school children aged 6 to 12 years.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…Two recent studies in central China reported the occurrence of E. bieneusi in 5.7% (39/683) of adult AIDS patients, 4.2% (29/683) of HIV-negative adult participants, 10.8% (8/74) of hospitalized case children with an average age of 20.7 months, and 3.2% (16/499) of control children with an average age of 42.6 months (8, 9). The pathogen was also detected in 22.5% (9/40) of in-hospital children with diarrhea (age unknown) in Changchun (10). The present study ascertained infection with the organism in diarrheic (25%, 1/4) and nondiarrheic (22.2%, 8/36) in-hospital children mostly aged Ͻ12 months and 5.6% (10/178) of healthy primary school children aged 6 to 12 years.…”
mentioning
confidence: 86%
“…Genotypic typing and phylogenetic analysis facilitated classification of the almost 200 genotypes identified thus far into genetic group 1 with zoonotic potential and several other host-adapted genetic clusters (4)(5)(6)(7). Infections with E. bieneusi in humans have been repeatedly reported worldwide, although epidemiologic data to indicate the prevalence and risk of human microsporidiosis in China are limited (8)(9)(10). The frequent and close contact of humans with livestock in China is of potential zoonotic concern (6,7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies in companion animals, such as dogs and cats, which are considered highrisk hosts for the zoonotic transmission of such diseases, remain scarce. One study by Zhang and colleagues reported two new genotypes of E. bieneusi in dogs in China (17). Likewise, studies in dogs and cats have been few in other parts of the world.…”
mentioning
confidence: 99%
“…To date, BEB6 has been usually derived from animals (especially sheep and cattle) (Ye et al 2015, Zhao et al 2015, but also identified in human and nonhuman primates in Henan Province (Wang et al 2013, Karim et al 2014b. Genotypes I and J reported in captive wildlife in Zhengzhou had also been detected in humans in Jilin, China (Zhang et al 2011). The novel genotypes (HNWW1 to HNWW5) showed only difference 1-3 bases from known zoonotic or potential zoonotic genotypes.…”
Section: Discussionmentioning
confidence: 99%